Self-reported anxiety in postgraduate students of Oral Pathology and Oral Medicine in Brazil: impacts and challenges for academic well-being - Maia-Lima, Marcos Paulo; Ferreira, Luiz Miguel; Nascimento, João Pedro Santos; Trezena, Samuel; de Oliveira, Fabrício Emanuel Soares; Duarte, Árlen Almeida; Martelli, Daniella Reis Barbosa; Alves, Fábio de Abreu; Almeida, Janete Dias [UNESP]; Santos, Jean Nunes Dos; Lopes, Marcio Ajudarte; de Aguiar, Maria Cassia Ferreira; et al. (Elsevier, 2025)
OBJECTIVE: To evaluate self-reported anxiety, the factors associated with its occurrence and its impact on the academic well-being of postgraduate students (Master and PhD) in Oral Pathology and Oral Medicine in Brazil. STUDY DESIGN: This multicenter observational study included postgraduate students in Oral Pathology and Oral Medicine from seven Brazilian universities. Data were collected using a 24-item online questionnaire that assessed sociodemographic, academic, and occupational characteristics, as well as symptoms of mental health disorders and were analyzed using SPSS® v27.0. Pearson's chi-square test and Poisson regression with robust variance were used to assess associations (P < .05; 95% CI). RESULTS: The results revealed that anxiety was the disorder with the highest prevalence (27.3%), followed by depression (15.1%) and burnout (8.6%). Female students (43.2%) were significantly more affected by mental health disorders. Postgraduate students' perception of excessive pressure from professors/supervisors (adjusted PR = 1.77, P = .026) and professional psychological support (adjusted PR = 11.74, P < .001) were significantly associated with anxiety. CONCLUSIONS: This study highlights a mental health crisis in this specialized field, driven by academic pressures, underscoring the need for institutional strategies, including structural changes, improved supervisor-student relationships, and increased accessibility and awareness of psychological support services to promote a healthier academic environment.